Vospominanija. [Vstup. stat'ja i pod red. A.L. Sidorova. Vstup. zamečanija I.V. Gessena. S predisl. M.I. Vitte. S kommentarijami R.Š. Genalina, B.V. Anan'iča, V.I. Bovykina i dr.] (Socekgiz, 1960)
S ukaz-mi. 1. (1849-1894) Detstvo. Carstvovanija Aleksandra II i Aleksandra III. LXXXI, 556 str.